From Tropical Fruit to Wine Glass: Innovation in Mangosteen Peel Wine Processing - Iswari, Febri Nandia Sri; Prasetyanto, Hermawan; Susilowati, Heni; Hermawan, Hary (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2024)
This study explores the innovation in processing mangosteen peel for wine production. Aiming to transform mangosteen peel waste into an alcoholic beverage commonly served in hotels and restaurants, the research employs fermentation to produce wine with an alcohol content of 10-15%. Data was collected through interviews and questionnaires, using purposive sampling and quantitative experimental methods. The results indicate that the mangosteen peel wine received positive feedback from panellists, suggesting a favourable reception across the taste, aroma, and colour aspects. These findings highlight the potential of mangosteen peel wine as an innovative product in the alcoholic beverage industry.